Attempted molecular detection of the thermally dimorphic human fungal pathogen Emergomyces africanus in terrestrial small mammals in South Africa. (9th September 2017) - Cronjé, Nadine; Schwartz, Ilan S; Retief, Liezl; Bastos, Armanda D S; Matthee, Sonja; Preiser, Wolfgang; Bennett, Nigel C; Maphanga, Tsidiso; Govender, Nelesh P; Colebunders, Robert; Kenyon, Chris
Abstract: The ecological niche of Emergomyces africanus ( formerly Emmonsia species), a dimorphic fungus that causes an AIDS-related mycosis in South Africa, is unknown. We hypothesized that natural infection with E. africanus occurs in wild small mammals. Using molecular detection with primers specific for E. africanus, we examined 1402 DNA samples from 26 species of mole-rats, rodents, and insectivores trapped in South Africa that included 1324 lung, 37 kidney, and 41 liver specimens. DNA of E. africanus was not detected in any animals. We conclude that natural infection of wild small mammals in South Africa with E. africanus has not been proven.